Association of GLP-1 receptor agonists and risk of pancreatitis: a pharmacovigilance study based on FAERS database - Bishakha, Adwiza Chakraborty (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.